Multicenter analytical evaluation of a high-sensitivity troponin T assay - Saenger, Amy; Beyrau, R.; Braun, S.; Cooray, R.; Dolci, A.; Freidank, H.; Giannitsis, Evangelos; Gustafson, S.; Handy, B.; Katus, Hugo; Melanson, S. E.; Panteghini, M.; et al. (Clinica chimica acta, 2011)
Background - High-sensitivity cardiac troponin assays are being introduced clinically for earlier diagnosis of acute myocardial infarction (AMI). We evaluated the analytical performance of a high-sensitivity cardiac troponin T assay (hscTnT, Roche Diagnostics) in a multicenter, international trial. - Methods - Three US and 5 European sites evaluated hscTnT on the Modular® Analytics E170, cobas® 6000, Elecsys 2010, and cobas® e 411. Precision, accuracy, reportable range, an inter-laboratory comparison trial, and the 99th percentile of a reference population were assessed. - Results - Total imprecision (CVs) were 4.6-36.8% between 3.4 and 10.3ng/L hscTnT. Assay linearity was up to 10,000ng/L and the limit of blank and detection were 3 and 5ng/L, respectively. The 99th percentile reference limit was 14.2ng/L (n=533). No significant differences between specimen types, assay incubation time, or reagent lots existed. A substantial positive bias (76%) exists between the 4th generation and hscTnT assays at the low end of the measuring range (<50ng/L). hscTnT serum pool concentrations were within 2SD limits of the mean of means in the comparison trial, indicating comparable results across multiple platforms and laboratories. - Conclusion - The Roche hscTnT assay conforms to guideline precision requirements and will likely identify additional patients with myocardial injury suspicious for AMI.
Gesehen am 30.09.2022